Blood, Sweat, and Fear: Violence at Work in the North American Auto Industry, 1960-80 - Milloy, Jeremy (UBC Press, 2017)
Going postal. We think of the rogue employee who snaps. But in [this book] Jeremy Milloy demonstrates that workplace violence never occurs in isolation. Using violence as a lens, he provides fresh and original insights into the everyday workings of capitalism, class conflict, race, and gender in the United States and Canada of the late twentieth century, bringing historical perspective to contemporary debates about North American violence. [The book] is the first full-length historical exploration of the origins and effects of individual violence in the automotive industry. Milloy’s gripping analysis spans 1960 to 1980, when North American auto plants were routinely the sites of fights, assaults, and even murders. He argues that the high levels of violence were primarily the result of workplace conditions – including on-the-job exploitation, racial tension, bureaucratization, and hypermasculinity – that made fear and loathing a shop-floor reality long before mass shootings attracted media attention in the 1980s. Workplace violence is typically the domain of management studies and psychology, but while we pass legislation and adopt best practices, the problem continues. Milloy’s explosive book reveals that workplace violence has been a constant aspect of class conflict – and that our understanding needs to go deeper. Blood, Sweat, and Fear will interest everyone concerned with the causes of workplace violence, and in particular scholars and students of labour history, sociology, sociological criminology, masculinity studies, and studies of race and of violence. --Publisher's description. Contents: Dripping with blood and dirt: confronting the history of workplace violence under capitalism -- Fights and knifings are becoming quite commonplace: Dodge main, 1965-80 -- The way boys and men took care of business: Windsor Chrysler plants -- The constant companion of all that earn their living here: workers, unions, and management respond -- Chrysler pulled the trigger: the courts and the press -- Out of the back streets and into the workplace: the discovery of workplace violence in the 1980s and 1990s.
Keywords: 20th century. Automobile industry and trade; 20th century. Automobile industry workers; 20th century. Violence; 20th century. Violence en milieu de travail; 20th century. Violence in the workplace; Aspect social; Canada; Conditions sociales; Histoire; History; Industrie et commerce; Social aspects; Social aspects. Genre/Form: History; Social conditions; United States; Violence in the workplace